Cellulose / magnetic composite particles and method for producing same
Cellulose/magnetic composite particles, formed by combining cellulose nanofibers with magnetic particles and incorporating surface holes, address the issues of coagulation and collection efficiency, enhancing adsorption performance.
Patent Information
- Application Number
- JP2020135197
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-08-07
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2040-08-07
AI Technical Summary
Cellulose nanofibers used as dry powder easily coagulate and lose their adsorption performance, and they are difficult to collect efficiently from dispersion.
Formation of cellulose/magnetic composite particles by combining cellulose nanofibers with magnetic particles, which can be collected using a magnet, and the particles may include surface holes formed by removing template particles during the spray-drying process.
The cellulose/magnetic composite particles can be efficiently collected and their adsorption performance is enhanced due to the magnetic properties and increased surface area provided by the surface holes.
Smart Images

Figure 0007649508000005 
Figure 0007649508000006 
Figure 0007649508000007
Abstract
Description
[Technical field]
[0001] The present invention relates to cellulose / magnetic material composite particles formed by combining cellulose nanofibers with magnetic material particles, a method for producing the same, and a method for collecting the cellulose / magnetic material composite particles. [Background technology]
[0002] As research and applications of cellulose nanofibers in the biochemistry field, there have been reported cases in which the adsorption of biologically active substances such as proteins through interactions between them and TEMPO-oxidized cellulose nanofibers (TOCN) (see Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 6159737 Summary of the Invention [Problem to be solved by the invention]
[0004] When cellulose nanofibers are used as a dry powder, for example, they tend to aggregate if they are simply left to dry, which reduces their performance as an adsorbent. For this reason, it is possible to form cellulose nanofibers into, for example, micro-sized particles by spray-drying a dispersion of cellulose nanofibers. However, cellulose particles made of cellulose nanofibers are difficult to collect from the dispersion, so there is a need to improve the collectability.
[0005] An embodiment of the present invention aims to improve the collection properties of cellulose particles made of cellulose nanofibers. [Means for solving the problem]
[0006] The present invention includes the embodiments set forth below. [1] A cellulose / magnetic material composite particle, which is a particle formed from cellulose nanofibers and contains magnetic material particles. [2] The cellulose / magnetic material composite particle according to [1], which has a plurality of holes on the particle surface that are traces of the removal of the template particle. [3] The cellulose / magnetic material composite particles according to [2], wherein the average particle size of the cellulose / magnetic material composite particles is 1 to 30 μm, and the average pore size of the holes is 1 / 200 to 1 / 5 of the average particle size of the cellulose / magnetic material composite particles. [4] The cellulose / magnetic material composite particles according to any one of [1] to [3], wherein the cellulose nanofibers have anionic functional groups. [5] An adsorbent comprising the cellulose / magnetic material composite particles according to any one of [1] to [4]. [6] A method for producing cellulose / magnetic material composite particles, comprising spray-drying a dispersion containing cellulose nanofibers and magnetic material particles. [7] A method for producing cellulose / magnetic material composite particles according to [6], comprising: obtaining cellulose / magnetic material / template composite particles in which the cellulose nanofibers, the magnetic material particles, and the template particles are composited by spray drying, in which the dispersion to be spray-dried contains template particles together with the cellulose nanofibers and the magnetic material particles; and dissolving the template particles contained in the obtained cellulose / magnetic material / template composite particles in an organic solvent. [8] A method for collecting the cellulose / magnetic material composite particles according to any one of [1] to [4] from a liquid in which the cellulose / magnetic material composite particles are dispersed, using a magnet. [9] A method for collecting cellulose / magnetic material composite particles, comprising the steps of: adsorbing a physiologically active substance to the cellulose / magnetic material composite particles in a liquid in which the cellulose / magnetic material composite particles described in any one of [1] to [4] are dispersed; and collecting the cellulose / magnetic material composite particles with the physiologically active substance adsorbed from the liquid using a magnet. Effect of the Invention
[0007] In an embodiment of the present invention, cellulose particles made of cellulose nanofibers are made to contain magnetic particles to form cellulose / magnetic composite particles, which allows the particles to be collected from the dispersion liquid using a magnet, thereby improving collectability. [Brief description of the drawings]
[0008] [Figure 1] (A) Schematic diagram of a cellulose / magnetic material / template composite particle. (B) Schematic diagram of a cellulose / magnetic material composite particle with holes left by the removal of the template particle. [Diagram 2] A conceptual diagram showing a method for collecting cellulose / magnetic composite particles. [Diagram 3] SEM image of cellulose / magnetic material composite particles in the first experimental example. [Figure 4] (A) SEM image of composite particles (PMMA / TOCN=1 / 1) of PMMA particles and cellulose nanofibers in Reference Example 1. (B) SEM image of porous cellulose particles in Reference Example 1 after dissolution and removal of PMMA particles. [Diagram 5] Graph showing the results of FT-IR measurement of the porous cellulose particles of Reference Example 1, the composite particles thereof before toluene treatment, and the cellulose particles and PMMA particles of Comparative Example 1. [Figure 6] 1 shows SEM images of composite particles of PMMA particles and cellulose nanofibers in Reference Examples 2 to 4 and the porous cellulose particles after dissolving and removing the PMMA particles. [Figure 7] (A) SEM image of composite particles (TOCN / Fe3O4 / PMMA=1 / 1 / 4) of PMMA particles, cellulose nanofibers, and magnetic particles of Example 5. (B) Cellulose / magnetic composite particles after dissolution and removal of PMMA particles of Example 5. (C) Enlarged image of a part of the same. [Figure 8] (A) SEM image of the cellulose / magnetic material composite particles (TOCN / Fe3O4 / PMMA=1 / 2 / 4) after dissolution and removal of the PMMA particles in Example 6. (B) Enlarged image of a portion thereof. [Figure 9] Graph showing the adsorption capacity of lysozyme for cellulose / magnetic material composite particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The cellulose / magnetic material composite particles according to this embodiment are particles formed from cellulose nanofibers and contain magnetic material particles.
[0010] It is preferable to use cellulose nanofibers that satisfy the following (a) to (c). (a) The number average fiber diameter is 3 nm or more and 100 nm or less. (b) Having a cellulose type I crystal structure. (c) The average aspect ratio is between 2 and 5,000.
[0011] The number average fiber diameter of (a) is more preferably 50 nm or less, further preferably 30 nm or less, and may be 10 nm or less. The number average fiber diameter can be measured as follows.
[0012] That is, an aqueous dispersion of cellulose nanofibers with a solid content of 0.05 to 0.1% by mass is prepared, and the aqueous dispersion is cast on a carbon film-coated grid that has been hydrophilized to prepare a sample for observation with a transmission electron microscope (TEM). When the sample contains fibers with a large fiber diameter, a scanning electron microscope (SEM) image of the surface cast onto glass may be observed. The sample for observation may be negatively stained with, for example, 2% by mass uranyl acetate. Then, the sample is observed with an electron microscope image at a magnification of 5000 times, 10000 times, or 50000 times depending on the size of the fibers that constitute the sample. In this case, an arbitrary axis of the image width is assumed in the obtained image, vertically and horizontally, and the sample and observation conditions (magnification, etc.) are adjusted so that 20 or more fibers cross the axis. After obtaining an observation image that satisfies this condition, two random axes are drawn vertically and horizontally on the image, and the fiber diameters of the fibers that cross the axis are visually read. In this way, at least three non-overlapping images of the surface area are taken with an electron microscope, and the fiber diameters of the fibers intersecting each of the two axes are read (thus, information on the diameters of at least 20 fibers x 2 x 3 = 120 fibers is obtained). The arithmetic mean of the fiber diameters obtained in this way is the number-average fiber diameter.
[0013] The presence of the above (b) cellulose type I crystal structure can be identified by the presence of typical peaks at two positions, around 2θ=14° to 17° and around 2θ=22° to 23°, in the diffraction profile obtained by wide-angle X-ray diffraction image measurement.
[0014] The average aspect ratio of (c) above is more preferably 50 or more, further preferably 100 or more, and may be 200 or more. The average aspect ratio is more preferably 1000 or less, and may be 500 or less. The average aspect ratio can be measured as follows.
[0015] That is, the number average fiber diameter is calculated according to the method described above. The number average fiber length of the cellulose nanofibers is also calculated from the same observation image. Specifically, the length from the start point to the end point of the fiber (fiber length) of at least 10 fibers is visually read. For branched fibers, the length of the longest part of the fiber is taken as the fiber length. The arithmetic mean of the fiber lengths thus obtained is calculated to be the number average fiber length. Using these values, the average aspect ratio is calculated according to the following formula. Average aspect ratio = number average fiber length (nm) / number average fiber diameter (nm)
[0016] The cellulose nanofibers preferably have anionic functional groups, which have a negative potential in liquid and therefore exhibit advantageous adsorption performance for adsorbates with positive potential.
[0017] Examples of the anionic functional group include at least one selected from the group consisting of a carboxy group, a phosphoric acid group, a sulfonic acid group, a nitric acid group, a boric acid group, and a sulfate group. In this specification, the term "carboxy group" refers to a concept that includes not only an acid type (-COOH) but also a salt type, i.e., a carboxyl group (-COOX, where X is a cation that forms a salt with a carboxylic acid), and the acid type and the salt type may be mixed. Similarly, the term "phosphate group, sulfonic acid group, nitric acid group, boric acid group, and sulfate group" refers to a concept that includes not only an acid type but also a salt type, and the acid type and the salt type may be mixed. The salt is not particularly limited, and examples thereof include alkali metal salts such as sodium salts and potassium salts, alkaline earth metal salts such as magnesium salts and calcium salts, onium salts such as ammonium salts and phosphonium salts, and amine salts such as primary amines, secondary amines, and tertiary amines.
[0018] The amount of anionic functional groups in the cellulose nanofibers is not particularly limited, and may be, for example, 0.5 to 3.0 mmol / g or 1.5 to 2.0 mmol / g per dry mass of the cellulose nanofibers. For example, in the case of a carboxy group, the amount of anionic functional groups is determined by preparing 60 mL of a cellulose nanofiber-containing slurry adjusted to a concentration of 0.1 to 1% by mass, adjusting the pH to about 2.5 with a 0.1 mol / L aqueous hydrochloric acid solution, dropping a 0.05 mol / L aqueous sodium hydroxide solution, measuring the electrical conductivity, and continuing until the pH reaches about 11. The amount of sodium hydroxide consumed in the neutralization stage of the weak acid where the change in electrical conductivity is gradual (V) according to the following formula. The amount of phosphate groups can also be measured by the same electrical conductivity measurement. Other anionic groups may also be measured by known methods. Amount of anionic functional group (mmol / g) = V (mL) × [0.05 / mass of cellulose nanofiber (g)]
[0019] In one embodiment, the cellulose nanofiber preferably has a carboxy group as an anionic functional group. Examples of cellulose nanofibers containing a carboxy group include oxidized cellulose nanofibers obtained by oxidizing the hydroxyl groups of glucose units in cellulose molecules, and carboxymethylated cellulose nanofibers obtained by carboxymethylating the hydroxyl groups of glucose units in cellulose molecules.
[0020] Oxidized cellulose nanofibers include those in which the hydroxyl group at the C6 position of the glucose unit in the cellulose molecule is selectively oxidized to a carboxyl group. The oxidized cellulose nanofibers are obtained by oxidizing natural cellulose such as wood pulp using a co-oxidant in the presence of an N-oxyl compound and subjecting it to defibration (fine processing). As the N-oxyl compound, a compound having a nitroxy radical, which is generally used as an oxidation catalyst, is used, for example, a piperidine nitroxyoxy radical, and in particular, 2,2,6,6-tetramethylpiperidinooxy radical (TEMPO) or 4-acetamide-TEMPO is preferred. Cellulose nanofibers oxidized with TEMPO are generally called TEMPO-oxidized cellulose nanofibers (TOCN). The oxidized cellulose nanofibers may have an aldehyde group or a ketone group in addition to the carboxyl group.
[0021] The cellulose nanofibers may be obtained by defibration treatment. The defibration treatment may be performed after or before the introduction of an anionic functional group. The defibration treatment can be performed by treating a dispersion of cellulose fibers using, for example, a homomixer, a high-pressure homogenizer, an ultrasonic dispersion processor, a beater, a disk refiner, a conical refiner, a double disk refiner, a grinder, or the like under high-speed rotation, to obtain a dispersion of cellulose nanofibers.
[0022] The cellulose / magnetic material composite particles according to the embodiment are obtained by compounding cellulose particles made of cellulose nanofibers with magnetic material particles. The magnetic material particles are compounded and integrated in a dispersed state with the cellulose nanofibers, and may be attached to the particle surface of the cellulose particles made of cellulose nanofibers or may be embedded inside the cellulose particles.
[0023] The magnetic particles are not particularly limited as long as they are particles made of a ferromagnetic material that can be attracted by a magnet, and examples of the magnetic particles include particles of metal oxides such as iron oxides such as Fe3O4 and γ-Fe2O3, metals such as iron, manganese, nickel, cobalt, chromium, and alloys thereof, metal salts such as various ferrites, ferritic or martensite stainless steel, amorphous alloys, silicon-iron soft magnetic crystals, and the like, and any one or more of these may be used in combination.
[0024] The average particle size of the magnetic particles is not particularly limited and is usually smaller than the average particle size of the template particles described below and the average pore size of the holes left after removal of the template particles, and may be, for example, 1 to 200 nm or 10 to 120 nm.
[0025] The ratio of cellulose nanofibers to magnetic particles is not particularly limited, but the mass ratio C / M of cellulose nanofibers (C) to magnetic particles (M) may be 0.1-10, 0.5-5, or 0.8-3.
[0026] The cellulose / magnetic composite particles according to the embodiment preferably have a plurality of holes on the particle surface that are the traces of the template particles removed. The holes are formed by dissolving and removing the resin template particles with an organic solvent, and are clearly distinguishable from holes due to unevenness or gaps on the particle surface of cellulose particles obtained by simply spray-drying a dispersion of cellulose nanofibers. By using the template particles, holes having a pore size according to the particle size can be formed. Therefore, holes having a desired pore size can be formed on the surface of the cellulose / magnetic composite particles to make them porous, and porous particles with an increased surface area can be easily obtained.
[0027] The above-mentioned holes remaining after removal are preferably provided on the particle surface in order to enhance the adsorption effect when used as an adsorbent, and may be provided both on the particle surface and inside the particle.
[0028] The shape of the hole corresponds to the shape of the template particle. When a spherical particle is used as the template particle, the hole that is the removal trace is partially spherical on the particle surface of the cellulose / magnetic composite particle and spherical inside the particle. Therefore, when a spherical template particle is used, the cellulose / magnetic composite particle has a partially spherical hole on its particle surface. Here, partially spherical means a shape that lacks a part of a sphere. However, since the hole at the removal trace may be deformed due to distortion of the cellulose / magnetic composite particle caused by the treatment after dissolving and removing the template particle, the above-mentioned spherical or partially spherical shape does not necessarily have to have a strictly spherical or partially spherical surface, and also includes a distorted shape after dissolving and removing.
[0029] From the viewpoint of ease of handling, the cellulose / magnetic material composite particles according to the embodiment are preferably micro-sized. More specifically, the average particle size of the cellulose / magnetic material composite particles is preferably 1 to 30 μm, more preferably 2 to 20 μm, and further preferably 3 to 15 μm.
[0030] When the holes are formed in the cellulose / magnetic material composite particles, the average pore size of the holes is not particularly limited, but is preferably 1 / 200 to 1 / 5, and more preferably 1 / 100 to 1 / 10, of the average particle size of the cellulose / magnetic material composite particles. For example, the average pore size of the holes may be 100 to 1000 nm, or 200 to 700 nm. Here, the average pore size of the holes refers to the average value of the pore size (opening size) on the particle surface.
[0031] The area ratio of the holes formed on the particle surface of the cellulose / magnetic material composite particles (hole ratio) is not particularly limited, and may be 5 to 75% or 10 to 60% as the ratio of the opening area of the holes to the surface area of the particle.
[0032] The nitrogen adsorption specific surface area (BET method) of the cellulose / magnetic material composite particles is not particularly limited, but is preferably 1 to 50 m 2 / g, more preferably 5 to 40m 2 / g, 10 to 30m 2 / g is also acceptable.
[0033] The zeta (ζ) potential of the cellulose / magnetic composite particles is not particularly limited. When the cellulose nanofiber has an anionic functional group, the cellulose / magnetic composite particles have a negative zeta potential, and can adsorb cationic organic compounds to the particle surface by electrostatic attraction. Here, the zeta potential is the potential at the slip surface of the electric double layer, and is also called the interfacial dynamic potential. The zeta potential of the cellulose / magnetic composite particles in pure water may be, for example, -100 to -10 mV, or -70 to -30 mV.
[0034] The cellulose / magnetic material composite particles according to the present embodiment are formed of cellulose nanofibers and magnetic material particles, and may be composed of only cellulose nanofibers and magnetic material particles, but may also contain other components. For example, when the template particles remain without being completely dissolved and removed, the resin constituting the template particles may be contained as another component.
[0035] The cellulose / magnetic material composite particles according to this embodiment can be produced by spray-drying a dispersion containing cellulose nanofibers and magnetic material particles. By spray-drying, a dry powder can be obtained without agglomerating the cellulose nanofibers, and the cellulose nanofibers and magnetic material particles can be composited.
[0036] The dispersion liquid used in spray drying is prepared by, for example, using water as a solvent and uniformly mixing and dispersing cellulose nanofibers and magnetic particles in the solvent. The concentration of cellulose nanofibers in the dispersion liquid is not particularly limited as long as cellulose particles can be formed by spray drying, and may be, for example, 0.01 to 5% by mass or 0.05 to 1% by mass. The concentration of magnetic particles is also not particularly limited, and may be, for example, 0.01 to 50% by mass or 0.1 to 10% by mass.
[0037] The ratio of cellulose nanofibers to magnetic particles in the dispersion may be 0.1 to 10, 0.5 to 5, or 0.8 to 3, in terms of the mass ratio C / M of cellulose nanofibers (C) to magnetic particles (M), similar to the ratio in the cellulose / magnetic composite particles.
[0038] Spray drying is a method for producing a dry powder by spraying a dispersion liquid into a gas and rapidly drying it, and can be performed using a known spray dryer. The drying temperature in spray drying is not particularly limited and may be, for example, 150 to 200°C.
[0039] In one embodiment, when producing cellulose / magnetic material composite porous particles having holes on the surface of the particles due to the above-mentioned removal, the production method includes the following steps. (Step 1) spray-drying a dispersion liquid containing cellulose nanofibers, magnetic particles, and template particles; and (Step 2) A step of dissolving the template particles contained in the cellulose / magnetic material / template composite particles obtained by spray drying in an organic solvent.
[0040] In this example, the dispersion to be spray-dried contains template particles together with cellulose nanofibers and magnetic particles. The template particles are particles that serve as a mold for forming holes in cellulose particles made of cellulose nanofibers to make them porous particles, and can be used without any particular limitation as long as they are resin particles that can be dissolved and removed by organic solvents, acids, alkalis, etc. after being composited with cellulose nanofibers. Both organic and inorganic materials can be used as the template particles. Examples of organic materials include resin particles such as acrylic resins such as polymethyl methacrylate and polymethyl acrylate, styrene resins such as polystyrene, vinyl resins such as polyvinyl alcohol, and polyester resins. Examples of inorganic materials include calcium carbonate that dissolves in acids, and SiO2 that dissolves in alkalis. These may be used alone or in combination of two or more.
[0041] The average particle size of the template particles is not particularly limited, but is preferably 100 to 1000 nm, more preferably 200 to 800 nm, and may be 300 to 700 nm.
[0042] The concentrations of the cellulose nanofibers and magnetic particles are as described above in the dispersion liquid prepared in step 1. The concentration of the template particles is not particularly limited and may be, for example, 0.01 to 20% by mass, or 0.1 to 10% by mass.
[0043] In the dispersion, the ratio of cellulose nanofibers to template particles is not particularly limited, but may be 0.5-10, or 1-6, in terms of the mass ratio T / C of template particles (T) to cellulose nanofibers (C).
[0044] In step 1, cellulose / magnetic material / template composite particles are obtained by combining cellulose nanofibers, magnetic particles, and template particles by spray drying. As shown in the conceptual diagram in Figure 1(A), the cellulose / magnetic material / template composite particles obtained by spray drying are integrated with a cellulose nanofiber as a matrix in which multiple template particles and magnetic particles are dispersed.
[0045] In the cellulose / magnetic material / template composite particles, the mass ratio C / M of the cellulose nanofibers (C) to the magnetic particles (M) may be, as described above, from 0.1 to 10, from 0.5 to 5, or from 0.8 to 3. The mass ratio T / C of the template particles (T) to the cellulose nanofibers (C), like the dispersion liquid, may be from 0.5 to 10, or from 1 to 6. The cellulose / magnetic material / template composite particles may contain any component other than these three components.
[0046] In step 2, the cellulose / magnetic material / template composite particles obtained above are treated with an organic solvent to dissolve and remove the template particles contained in the composite particles. The organic solvent is not particularly limited as long as it can dissolve the template particles without dissolving the cellulose nanofibers, and examples of the organic solvent include toluene, xylene, methyl ethyl ketone, alcohol, and N,N-dimethylformamide, although it depends on the type of resin that constitutes the template particles. Examples of the acid include hydrochloric acid and sulfuric acid. Examples of the alkali include an aqueous solution of sodium hydroxide and an aqueous solution of potassium hydroxide.
[0047] After treating with an organic solvent to dissolve and remove the template particles, the particles may be separated from the organic solvent and dried to obtain cellulose / magnetic material composite porous particles. Figure 1(B) is a conceptual diagram of a cellulose / magnetic material composite porous particle, in which magnetic particles are composited to particles made of cellulose nanofibers, and multiple holes are provided on the particle surface as traces of the removed template particles.
[0048] The cellulose / magnetic composite particles according to the embodiment can be used, for example, as an adsorbent or carrier for physiologically active substances such as proteins. More specifically, as an adsorbent for physiologically active substances, it can purify and separate physiologically active substances such as proteins, and can also be used as a packing material for column chromatography to purify physiologically active substances. It may also be used as a carrier for carrying enzymes and carrying out reactions. When cellulose nanofibers having anionic functional groups are used, they are preferably used as an adsorbent for physiologically active substances having an isoelectric point of more than 7.
[0049] The physiologically active substance is not particularly limited, and examples thereof include proteins, hormones, nucleic acids (DNA, RNA), sugars, sugar chains, vitamins, peptides, etc. Examples of proteins include enzymes, antibodies, receptors, etc.
[0050] The collection method according to the embodiment is a method for collecting (recovering) the cellulose / magnetic material composite particles from a liquid in which the cellulose / magnetic material composite particles are dispersed, using a magnet.
[0051] Figure 2 is a conceptual diagram of a method for collecting cellulose / magnetic composite particles. As shown in Figure 2(A), when cellulose / magnetic composite particles are dispersed in a liquid such as water (including aqueous solutions such as buffer solutions) or an organic solvent, by using a magnet, the cellulose / magnetic composite particles can be attracted to the wall of a container by its magnetic force and collected, as shown in Figure 2(B), so that they can be easily separated from the liquid. The magnet may be a permanent magnet or an electromagnet.
[0052] This collection method can be used in various situations where cellulose / magnetic composite particles are collected from a liquid. For example, it may be used in recovering cellulose / magnetic composite particles from an organic solvent after dissolving and removing the template particles in the above step 2 in the method for producing cellulose / magnetic composite particles.
[0053] In addition, when used as an adsorbent for a physiologically active substance as described above, it may be used to extract a specific physiologically active substance from a liquid. That is, after a physiologically active substance is adsorbed to the cellulose / magnetic material composite particles in a liquid in which the cellulose / magnetic material composite particles are dispersed, the cellulose / magnetic material composite particles to which the physiologically active substance is adsorbed may be collected from the liquid using a magnet.
[0054] Specifically, as an example, a physiologically active substance can be extracted by a method including the following steps: dispersing cellulose / magnetic composite particles in an aqueous solution containing a specific physiologically active substance and allowing the specific physiologically active substance to be adsorbed onto the cellulose / magnetic composite particles, collecting and removing the cellulose / magnetic composite particles with the physiologically active substance adsorbed from the aqueous solution using a magnet, and desorbing the physiologically active substance from the cellulose / magnetic composite particles removed from the aqueous solution. An example of a method for desorbing a physiologically active substance from a cellulose / magnetic composite particle is a method in which the cellulose / magnetic composite particle with the physiologically active substance adsorbed is placed in a buffer solution set to a pH different from that of the adsorption step (a pH that desorbs the physiologically active substance). EXAMPLES
[0055] The present invention will be explained in more detail below with reference to examples, but is not limited to these.
[0056] [Measurement method] (1) Number average fiber diameter of cellulose nanofibers The number-average fiber diameter of the cellulose nanofibers was observed using a transmission electron microscope (TEM) (JEM-1400, manufactured by JEOL Ltd.). That is, the sample was cast on a hydrophilically treated carbon film-coated grid, and the number-average fiber diameter was calculated from the TEM image (magnification: 10,000 times) negatively stained with a 2% by mass uranyl acetate aqueous solution according to the method described above.
[0057] (2) Average aspect ratio of cellulose nanofibers The number average fiber length of the cellulose nanofibers was calculated according to the method described above using the observation samples prepared in the same manner as in the measurement of the number average fiber diameter. The average aspect ratio was then calculated according to the above formula using the number average fiber diameter and number average fiber length values.
[0058] (3) Crystal structure of cellulose nanofibers The diffraction profile of the sample was measured using an X-ray diffractometer (Rigaku Corporation, RINT-Ultima3). If typical peaks were observed at two positions, around 2θ = 14° to 17° and 2θ = 22° to 23°, the crystal structure (type I crystal structure) was evaluated as "present," and if no peaks were observed, the sample was evaluated as "absent."
[0059] (4) Carboxylic group content of cellulose nanofibers 0.25 g of the sample was dispersed in water to prepare 60 mL of an aqueous dispersion. The pH was adjusted to about 2.5 with 0.1 M aqueous hydrochloric acid, and then 0.05 M aqueous sodium hydroxide was added dropwise to measure the electrical conductivity, and the amount of carboxyl groups was calculated according to the method described above.
[0060] (5) Average particle size of cellulose / magnetic composite particles and template particles The average particle size of the cellulose / magnetic composite particles was measured by taking pictures at 5,000 to 20,000 times magnification with an SEM (scanning electron microscope: S-5000, Hitachi High-Technologies Corporation, 20 kV condition), randomly selecting 200 or more particles, measuring their diameters, and calculating the average value. The average particle size of the template particles is the volume particle size (D50) value when the cumulative frequency becomes 50% of the total in the cumulative distribution function of the volume particle size obtained from DLS (dynamic light scattering particle size distribution measurement device), and was measured by dynamic light scattering using Malvern's "Zetasizer nano zs". The sample concentration was 0.2 mg / mL, and pure water was used as the solvent.
[0061] (6) Average particle size of magnetic particles The average particle size of the magnetic particles was determined by taking photographs at a magnification of 5,000 to 20,000 times using an SEM (scanning electron microscope: S-5000, manufactured by Hitachi High-Technologies Corporation, 20 kV), randomly selecting 200 or more particles, measuring their diameters, and calculating the average value.
[0062] (7) Average pore size of holes left after removal of template particles The average pore size of the cellulose / magnetic composite particles was determined by taking photographs at a magnification of 5,000 to 20,000 times using an SEM (scanning electron microscope: S-5000, manufactured by Hitachi High-Technologies Corporation, 20 kV), randomly selecting 350 holes from the particles, measuring their opening diameters, and calculating the average value.
[0063] (8) Area ratio of holes on the particle surface of cellulose / magnetic material composite particles (hole ratio) Photographs of any 10 cellulose / magnetic material composite particles were taken at magnifications of 5,000 to 20,000 using an SEM (scanning electron microscope: S-5000, Hitachi High-Technologies Corporation, 20 kV). The area of the particle shown in the photograph (the area inside the outline of the particle) and the sum of the opening area of all removal traces within the outline (the area of the openings that can be read from the photograph) were calculated using image analysis software, and the average ratio (percentage) of the opening area of the holes to the area of the particle was calculated as the hole ratio.
[0064] (9) Zeta potential The measurement was performed using Malvern's Zetasizer nano zs at 0.2 mg / mL in pure water at pH 7.0 and at a temperature of 25°C.
[0065] (10) BET value The nitrogen adsorption specific surface area of each particle by the BET method was measured by measuring the nitrogen adsorption isotherm at 77K using a capacity measuring device (BELSORP28SA, manufactured by BELL).
[0066] (11) FT-IR Measurement The chemical composition of each particle was analyzed by FT-IR (Shimadzu Corporation, FT-IR8700).
[0067] [First Experimental Example] (1) Raw materials TOCN: TEMPO-oxidized cellulose nanofiber (LeoCrysta I-2SX, Daiichi Kogyo Seiyaku Co., Ltd., cellulose concentration: 2% by mass, cellulose I-type crystal structure: "present", number-average fiber diameter: 4 nm, average aspect ratio: 280, carboxyl group amount: 1.9 mmol / g) ·Fe3O4 particles: Toda Kogyo Co., Ltd. Manufacturing (Average particle size: 100nm)
[0068] (2) Operation TOCN was mixed with pure water, and ultrasonic dispersion (IKA, T10 ULTRA-TURRAX S0004) was performed for 20 minutes to prepare an aqueous dispersion with a TOCN solid content of 0.08% by mass. Next, Fe3O4 particles were added to the aqueous dispersion so that the concentration was 0.02% by mass, and similar ultrasonic dispersion was performed for 40 minutes to prepare an aqueous dispersion containing TOCN and Fe3O4 particles (TOCN / Fe3O4 (mass ratio) = 4 / 1). The obtained aqueous dispersion was spray-dried using a spray dryer (BUCHI, Mini Spray Dryer B-290) to composite the TOCN and Fe3O4 particles, and the cellulose / magnetic composite particles (TOCN / Fe3O4 = 4 / 1) of Example 1 were obtained (yield: 52.8% by mass). The spray drying was performed at an inlet temperature of 180°C, a liquid flow rate of 2.5 mL / min, and a gas flow rate of 357 L / hour.
[0069] The amount of Fe3O4 particles added was adjusted so that the solid mass ratio of TOCN to Fe3O4, TOCN / Fe3O4, was 2 / 1 in Example 2, 1 / 1 in Example 3, and 1 / 2 in Example 4, and the cellulose / magnetic material composite particles were otherwise prepared in the same manner as in Example 1. The yield of the cellulose / magnetic material composite particles was 55.5% by mass in Example 2, 52.1% by mass in Example 3, and 42.1% by mass in Example 4.
[0070] As Comparative Example 1, cellulose particles were prepared in the same manner as in Example 1, except that no Fe3O4 particles were added.
[0071] (3) Measurement results SEM images of each particle obtained are shown in FIG. 3. In FIG. 3, "T / F" means TOCN / Fe3O4 (mass ratio). FIG. 3(A) is an image of the cellulose particles of Comparative Example 1, and FIG. 3(B) is a partially enlarged image thereof. No Fe3O4 particles were observed in the cellulose particles of Comparative Example 1. FIG. 3(C), (E), (G) and (I) are images of the cellulose / magnetic material composite particles of Examples 1 to 4, respectively, and FIG. 3(D), (F), (H) and (J) are partially enlarged images of the particles of Examples 1 to 4, respectively. As shown in these images, when Fe3O4 particles were added to the dispersion to be spray-dried, Fe3O4 particles were present on the surface of the obtained cellulose / magnetic material composite particles, and it was confirmed that the Fe3O4 particles were composited. In addition, an increase in Fe3O4 particles was observed on the surface of the cellulose particles as the concentration of Fe3O4 particles in the dispersion increased.
[0072] The average particle size and nitrogen adsorption specific surface area of the cellulose / magnetic material composite particles of Examples 1 to 4 and the cellulose particles of Comparative Example 1 were measured, and the results are shown in Table 1 below.
[0073] [Table 1]
[0074] [Second Experimental Example] A collection test using a magnet was carried out for the cellulose / magnetic composite particles of Examples 1 to 4. 50 mL of solvent and 10 mg of cellulose / magnetic composite particles were placed in a 50 mL glass vial to prepare a cellulose / magnetic composite particle dispersion with a concentration of 0.2 mg / mL. As the solvent, (a) pure water, (b) ethanol, and (c) a pH 9 buffer solution (a mixture of NH4OH: 0.1 M 5 ml, NH4Cl: 0.2 M 1.07 g, NaOH: 0.02 M 10 ml, and water 85 ml) were used. A neodymium magnet (diameter 2.5 cm, height 15 cm) with a magnetic flux density of 0.5 Tesla was brought into contact with the side of the vial as shown in FIG. 2(B), and the cellulose / magnetic composite particles in the dispersion were collected on the side of the vial. The time until the collection of the cellulose / magnetic composite particles was completed (collection time) was measured by observing until the supernatant became transparent.
[0075] The results are shown in Table 2. The higher the ratio of Fe3O4 particles in the cellulose / magnetic composite particles, the shorter the collection time. In addition, the collection time was shorter when the dispersion was in ethanol than in water.
[0076] [Table 2]
[0077] [Third Experimental Example] (1) Raw materials · TOCN: Same as the first embodiment. PMMA particles: polymethyl methacrylate particles (Sekisui Chemical Co., Ltd., average particle size: 503 nm)
[0078] (2) Operation TOCN and PMMA particles were mixed with pure water to prepare an aqueous dispersion (PMMA / TOCN (mass ratio) = 1 / 1) with a solid content concentration of 0.08 mass% for each of TOCN and PMMA. At that time, ultrasonic dispersion (IKA, T10 ULTRA-TURRAX S0004) was performed for 1 hour to uniformly disperse the particles. The obtained aqueous dispersion was spray-dried using a spray dryer (BUCHI, Mini Spray Dryer B-290) to obtain composite particles of TOCN and PMMA particles. The spray drying was performed at an inlet temperature of 180°C, a liquid flow rate of 2.5 mL / min, and a gas flow rate of 357 L / hour. 0.12 parts by mass of the obtained composite particles were added to 17.3 parts by mass of toluene and stirred at 100°C for 15 minutes to dissolve and remove the PMMA particles in the composite particles. The particles were then collected from the toluene and dried to obtain porous cellulose particles of Reference Example 1 (yield: 49.1% by mass).
[0079] Porous cellulose particles were prepared in the same manner as in Reference Example 1, except for adjusting the amount of PMMA particles added so that the mass ratio of the PMMA particles to the solid content of TOCN, PMMA / TOCN, was 2 / 1 in Reference Example 2, 3 / 1 in Reference Example 3, and 4 / 1 in Reference Example 4. The yield of the porous cellulose particles was 57.5 mass% in Reference Example 2, 51.2 mass% in Reference Example 3, and 48.0 mass% in Reference Example 4.
[0080] (3) Measurement results For Reference Example 1, SEM images of the particles before and after toluene treatment are shown in Figure 4. The image before toluene treatment shown in Figure 4(A) shows that composite particles were obtained in which multiple PMMA particles were integrated with cellulose nanofibers. The image after toluene treatment shown in Figure 4(B) shows that the PMMA particles were dissolved and removed, resulting in porous cellulose particles with multiple partially spherical holes formed on the particle surface.
[0081] SEM images of the particles before and after toluene treatment for Reference Examples 2 to 4 are shown in Fig. 6. In contrast to the images of the composite particles before toluene treatment shown in Fig. 6(A), (C), and (E), the images after toluene treatment shown in Fig. 6(B), (D), and (F) show that the PMMA particles were dissolved and removed, and multiple partially spherical holes were formed on the particle surfaces, thereby obtaining porous cellulose particles with an increased surface area.
[0082] The average particle size, average pore size, nitrogen adsorption specific surface area by BET method, and hole ratio of the porous cellulose particles of Reference Examples 1 to 4 were measured, and the results are shown in Table 3 below, along with the average particle size and nitrogen adsorption specific surface area of the cellulose particles of Comparative Example 1 above.
[0083] [Table 3]
[0084] The zeta potential was measured for the porous cellulose particles of Reference Example 1 and the composite particles thereof before the toluene treatment. The zeta potential was also measured for the cellulose particles of Comparative Example 1. The measurement results of the zeta potential are as follows, and the absolute value of the zeta potential of the porous cellulose particles of Reference Example 1 was slightly smaller than that of the composite particles before the toluene treatment. The zeta potential of the porous cellulose particles is equivalent to that of the cellulose particles of Comparative Example 1 that are not composited with PMMA particles, and it is clear that the particles are made of cellulose nanofibers. Porous cellulose particles of Reference Example 1: -54.3 mV Composite particles before toluene treatment in Reference Example 1: -59.5 mV Cellulose particles of Comparative Example 1: -55.3mV
[0085] FT-IR measurements were carried out on the porous cellulose particles of Reference Example 1, the composite particles thereof before toluene treatment, the cellulose particles of Comparative Example 1, and the PMMA particles. The results are shown in Figure 5. In Figure 5, "PMMA / TOCN=1" indicates the measurement results for the composite particles before toluene treatment, "TOCN porous" for the porous cellulose particles after toluene treatment, "TOCN" for the cellulose particles of Comparative Example 1, and "PMMA" for the PMMA particles. Wave number 1700 cm -1 The absorption due to PMMA was observed near the upper limit, and this was smaller in the case of the porous cellulose particles, confirming the dissolution and removal of the PMMA particles.
[0086] [Fourth Experimental Example] (1) Raw materials ·TOCN, Fe3O4 particles: Same as the first experimental example. PMMA particles: Same as in the third experimental example.
[0087] (2) Operation TOCN and PMMA particles were mixed with pure water and ultrasonically dispersed (IKA, T10 ULTRA-TURRAX S0004) for 20 minutes to prepare an aqueous dispersion with a TOCN solids concentration of 0.08% by mass and a PMMA concentration of 0.32% by mass. Next, Fe3O4 particles were added to the aqueous dispersion to a concentration of 0.08% by mass, and similar ultrasonic dispersion was performed for 40 minutes to prepare an aqueous dispersion containing TOCN, Fe3O4 particles, and PMMA particles (TOCN / Fe3O4 / PMMA (mass ratio) = 1 / 1 / 4).
[0088] The obtained aqueous dispersion was spray-dried using a spray dryer (Buchi Corporation, Mini Spray Dryer B-290) to obtain composite particles of TOCN, Fe3O4 particles, and PMMA particles. The spray drying was performed at an inlet temperature of 180°C, a liquid flow rate of 2.5 mL / min, and a gas flow rate of 357 L / hr. 0.12 parts by mass of the obtained composite particles were added to 17.3 parts by mass of toluene in a vial and stirred at 100°C for 30 minutes to dissolve and remove the PMMA particles in the composite particles.
[0089] Thereafter, the particles were collected from the toluene using a magnet and dried to obtain the cellulose / magnetic composite particles of Example 5 (yield: 62.5% by mass). For the collection using a magnet, a neodymium magnet (diameter 2.5 cm, height 15 cm) with a magnetic flux density of 0.5 Tesla was brought into contact with the side of the vial at room temperature for 30 to 1080 minutes to collect the cellulose / magnetic composite particles. After confirming that the supernatant was transparent, the toluene in the vial was removed. The cellulose / magnetic composite particles in the vial were washed with toluene, redispersed in ethanol, and dried at normal pressure at 60°C for 1 hour.
[0090] The amount of Fe3O4 particles added was adjusted so that the mass ratio of TOCN, Fe3O4 particles, and PMMA particles, TOCN / Fe3O4 / PMMA, was 1 / 2 / 4, and the rest of the procedure was the same as in Example 5 to prepare the cellulose / magnetic material composite particles of Example 6 (yield: 48.5% by mass).
[0091] (3) Measurement results As shown in Figure 7(A), the particles in Example 5 before the toluene treatment were cellulose nanofibers combined with Fe3O4 particles and PMMA particles. As shown in Figure 7(B), the particles after the toluene treatment had PMMA particles removed, and had multiple partially spherical holes on the surface that were traces of the PMMA particles removed, confirming the generation of cellulose / magnetic material composite porous particles. In addition, as shown in Figure 7(C), it was confirmed that iron oxide (Fe3O4 particles) was attached not only to the particle surface of the cellulose / magnetic material composite particles but also inside the holes.
[0092] Figure 8 shows SEM images of the cellulose / magnetic material composite particles of Example 6. As shown in Figure 8(A), the cellulose / magnetic material composite particles of Example 6 also had multiple partially spherical holes on the surface, which were traces of the PMMA particles being removed. In addition, as shown in Figure 8(B), iron oxide (Fe3O4 particles) was attached to the particle surface and inside the holes of the cellulose / magnetic material composite particles.
[0093] The cellulose / magnetic material composite particles of Examples 5 and 6 were measured for average particle size, average pore size, nitrogen adsorption specific surface area, hole ratio and zeta potential, and the results are shown in Table 4 below.
[0094] [Table 4]
[0095] [Fifth Experimental Example: Evaluation of Protein Adsorption Performance] (1) Raw materials · Lysozyme, from chicken egg white: MP Biomedical (Zeta potential: 7.8 mV, size: 4.5 x 3.0 x 3.0 nm, isoelectric point: 11). Cellulose / magnetic material composite particles: the cellulose / magnetic material composite particles of Example 5. Cellulose particles 1: Cellulose particles of Comparative Example 1. Cellulose particles 2: Cellufine C-500 (cellulose particles with carboxymethyl groups) manufactured by JNC Corporation
[0096] (2) Operation 10 mg of cellulose / magnetic composite particles, cellulose particle 1, or cellulose particle 2 was added to 50 mL of 0.4 g / L lysozyme solution dissolved in phosphate buffer, and the mixture was stirred using a shaker, and sampling was performed at stirring times of 5, 10, 20, 30, 60, 90, and 120 minutes. The supernatant was separated from the sampled samples. Separation of the particles and the supernatant was performed by centrifugation (8000 rpm, 5 minutes) for cellulose particle 1 and cellulose particle 2. Meanwhile, for the cellulose / magnetic composite particles, the sampled sample was separated into the cellulose / magnetic composite particles and the supernatant using a neodymium magnet.
[0097] The absorbance of the obtained supernatant was measured by ultraviolet-visible-near infrared spectroscopy (281 nm), and the amount of free protein in the supernatant (C1) was quantified by comparing it with a separately prepared calibration curve, and the adsorption capacity of lysozyme was calculated from the result. The adsorption capacity of lysozyme was calculated by subtracting the amount of protein in the supernatant (C1) from the mass of lysozyme added (C0) to obtain the adsorption amount of lysozyme (mg), and the adsorption amount of lysozyme per unit mass of the adsorbent added was calculated using the following formula. Amount of lysozyme adsorbed (mg) = C0-C1 Adsorption capacity of lysozyme (mg / g) = (C0-C1) (mg) / mass of adsorbent added (g)
[0098] (3) Measurement results The results are shown in Figure 9. The cellulose / magnetic material composite particles of Example 5 had a lysozyme adsorption capacity of 852 mg / g. This was approximately 1.4 times the adsorption capacity of cellulose particles 1 of Comparative Example 1, which were not porous using template particles, and commercially available cellulose particles 2, and the particles had excellent protein adsorption performance.
[0099] Although several embodiments of the present invention have been described above, these embodiments are presented as examples and are not intended to limit the scope of the invention. These embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the gist of the invention. These embodiments and their omissions, substitutions, modifications, etc. are included in the scope and gist of the invention as well as the invention and its equivalents described in the claims.
Claims
1. A cellulose / magnetic material composite particle formed from cellulose nanofibers, containing magnetic material particles and having a plurality of holes on the particle surface which are traces of the removal of a template particle.
2. The cellulose / magnetic material composite particles according to claim 1, wherein the average particle size of the cellulose / magnetic material composite particles is 1 to 30 μm, and the average pore size of the holes is 1 / 200 to 1 / 5 of the average particle size of the cellulose / magnetic material composite particles.
3. The cellulose / magnetic material composite particle according to claim 1 or 2, wherein the cellulose nanofiber has an anionic functional group.
4. An adsorbent comprising the cellulose / magnetic material composite particles according to any one of claims 1 to 3.
5. spray-drying a dispersion liquid containing cellulose nanofibers, magnetic particles, and template particles; Obtaining cellulose / magnetic material / template composite particles in which the cellulose nanofibers, the magnetic material particles, and the template particles are composited by spray drying; and dissolving the template particles contained in the obtained cellulose / magnetic material / template composite particles in an organic solvent; A method for producing cellulose / magnetic material composite particles, comprising:
6. A method for collecting cellulose / magnetic composite particles, which are particles formed from cellulose nanofibers having anionic functional groups and contain magnetic particles, from a liquid in which the cellulose / magnetic composite particles are dispersed using a magnet.
7. A method for collecting cellulose / magnetic composite particles, comprising the steps of: adsorbing a physiologically active substance to a cellulose / magnetic composite particle in a liquid in which the cellulose / magnetic composite particle, the cellulose / magnetic composite particle being a particle formed from cellulose nanofibers having anionic functional groups and including magnetic particles, is dispersed; and collecting the cellulose / magnetic composite particle with the physiologically active substance adsorbed from the liquid using a magnet.
Citation Information
Patent Citations
Manufacture of semiconductor device
JP1986059737A
Production of cellulosic cellular particle
JP1991231942A
Spherical porous cellulose particle comprising chitin or deacetylated chitin and cellulose, and preparation thereof
JP1992057836A
Cellulose porous body and its production
JP1997176327A
Novel method and system for magnetic separation
JP2016536132A